Guía metodológica para el diseño e implementación de planes de seguridad vial (2016)
The degree work is the development of a methodology, practical and understandable that can be used by companies to make the design and implementation of strategic road safety plan, which aims to reduce accidents on the roads guide. the correlation of the frames is: Legal, placing resolution 1565 of 2014, the Ministry of transport, which, the Methodological Guide for the Strategic Road Safety Plan is issued. PDCA cycle theoretician and policy with Standard Internment ISO 3901, Management System Road Safety. Forming consistency and scope of the guide. They develop one by one the pillars of road safety: strengthening institutional management, measures on human behavior, measures on vehicles, secure infrastructure and care for victims; by definition, examples, flowcharts, recommendations and annexes, which will allow the company to make the set design to the need and regulations.